Retrospective evaluation of Micrurus fulvius (Eastern coral snake) envenomation and the use of mechanical ventilation in dogs and a cat (2011–2016): 8 cases. Issue 6 (18th October 2019) - Campos, Samantha; Allen‐Durrance, Ashley E.; Schaer, Michael; Lynch, Alex
Abstract: Objective: To describe the use of mechanical ventilation (MV) in the management of Eastern coral snake envenomation in 7 dogs and a cat. Design: Retrospective study (2011–2016). Setting: University teaching hospital. Animals: Seven dogs and 1 cat receiving MV for ventilatory failure secondary to Eastern coral snake envenomation. Interventions: None. Measurement and Main Results: The medical records of 8 animals that received MV following Eastern coral snake envenomation were reviewed. Data collected included signalment, time to veterinary assessment, physical and laboratory characteristics at arrival, clinical course during hospitalization, management including antivenom administration, MV settings, duration of ventilation, length of hospitalization, cost of care, and survival to discharge. The mean ± SD age was 4 ± 3.2 years. Median (range) time to onset of clinical signs was 30 (5–240) minutes. Coral snake antivenom was administered to 7 of the 8 animals following arrival at a median (range) of 30 (5–90) minutes. All animals had progressive hypoventilation and received MV, specifically volume controlled, synchronized intermittent mandatory ventilation with pressure support. The median (range) duration of MV was 58 (25–84) hours and the median (range) duration of hospitalization was 8.2 (6–11) days. Ventilator associated complications occurred in all animals, but overall outcome was excellent with 7 of 8 surviving to discharge. No dog, but the 1 cat, had an adverse reaction to antivenom. Conclusions: Ventilatory failure secondary to Eastern coral snake envenomation necessitating MV carries an excellent prognosis and is better than reported for other causes of lower motor neuron disease. Successful response to ventilation was achieved even with associated complications being common in this cohort of animals.